APLIKASI REGRESI COX PROPORTIONAL HAZARD PADA SINTASAN PASIEN DIABETES MELITUS - DEWI, IDA AYU PUTU RATNA; SUCIPTAWATI, NI LUH PUTU; TASTRAWATI, NI KETUT TARI (E-Jurnal Matematika; Vol 7 No 3 (2018)DO - 10.24843/MTK.2018.v07.i03.p215, 2018)
Diabetes melitus is one of the deadliest diseases in the world. Until now, the incidence and the mortality rate due to diabetes melitus is still very high. To determine the survival of diabetes melitus patients, the significant factors that affect must be obtained by applying Cox Proportional Hazard regression method. The purpose of this study is to determine the chances of probability of diabetes melitus patients and to determine the significant factors that affect on the survival of diabetes melitus patients. The variables used in this study are the length of time of inpatient of diabetes melitus patient in RSUD Wangaya as dependent variable, while age, gender, genetic, blood glucose status, accompanying disease, pain, diabetes drug and insulin, and body mass index as independent variable. Through the analysis of this study we obtained the significant factors that affect the survival of diabetes melitus patients are sex, blood glucose status, and accompanying diseases .